Global crises and the crisis of global leadership - Gill, Stephen, 1950- (Cambridge : Cambridge University Press, 2012)
'This groundbreaking collection on global leadership features innovative and critical perspectives by scholars from international relations, political economy, medicine, law and philosophy, from North and South. The book's novel theorization of global leadership is situated historically within the classics of modern political theory and sociology, relating it to the crisis of global capitalism today. Contributors reflect on the multiple political, economic, social, ecological and ethical crises that constitute our current global predicament. The book suggests that there is an overarching condition of global organic crisis, which shapes the political and organizational responses of the dominant global leadership and of various subaltern forces. Contributors argue that to meaningfully address the challenges of the global crisis will require far more effective, inclusive and legitimate forms of global leadership and global governance than have characterized the neoliberal era'--
Machine generated contents note: Part I. Concepts of Global Leadership and Dominant Strategies: 1. Leaders and led in an era of global crises Stephen Gill; 2. Leadership, neoliberal governance and global economic crisis: a Gramscian analysis Nicola Short; 3. Private transnational governance and the crisis of global leadership A. Claire Cutler; Part II. Changing Material Conditions of Existence and Global Leadership - Energy, Climate Change and Water: 4. The crisis of petro-market civilization - the past as prologue? Tim Di Muzio; 5. Global climate change, human security, and the future of democracy Richard A. Falk; 6. The emerging global freshwater crisis and the privatization of global leadership Hilal Elver; Part III. Global Leadership Ethics, Crises and Subaltern Forces: 7. Global leadership, ethics and global health - the search for new paradigms Solomon R. Benatar; 8. Global leadership and the Islamic world - crisis, contention and challenge Mustapha Kamal Pasha; 9. Public and insurgent reason - adjudicatory leadership in a hyper-globalizing world Upendra Baxi; Part IV. Prospects for Alternative Forms of Global Leadership: 10. Global democratization without hierarchy or leadership? The world social forum in the capitalist world Teivo Teivainen; 11. After neoliberalism - left versus right projects of leadership in the global crisis Ingar Solty; 12. Crises, social forces and the future of global governance - implications for progressive strategy Adam Harmes; 13. Organic crisis, global leadership and progressive alternatives Stephen Gill.
Includes bibliographical references (p. 259-286) and index.
Keywords: Political leadership; Leadership; Financial crises -- History -- 21st century; Crises -- History -- 21st century